Assessment of Known Risk Factors for Dengue Transmission in Haraincha Village Development Committee of Eastern Nepal - Parajuli, S.B.; KC, Heera (Birat Journal of Health Sciences, 2017)
Introduction Currently dengue is a worldwide public health problem. Almost half of world’s populations are at risk of dengue. The first case was reported from Nepal in 2004, since then major outbreaks occurred in the year 2006, 2010, 2012 and 2013. As Jhapa district had outbreak in 2012 and 2013, there is a high chance of outbreak in Morang district also. There might be presence of many known risk factor for dengue transmission at Haraincha Village Development Committee (VDC). Objective To assess the known risk factor associated with dengue transmission in Haraincha Village Development Committee of Morang district of Eastern Nepal. Methodology Community based cross-sectional study was conducted from th th 15 October 2013 to 30 November 2013 in Haraincha VDC of Morang district. The data was collected from 122 households by means of interview using a semi structured questionnaires and direct observation after taking informed consent. We observed the known risk factor of possible dengue transmission. Data were entered into Microsoft excel and analyzed by using SPSS. Results The mean age of the respondent was 38 years with male predominance (61.5%). Only 7.4% were illiterate. The major occupation was agriculture (45.9%). Fifty four percent were above the poverty line. Two percent had history of dengue contracted outside the country. Common risk factors observed were poor drainage system (79%), poor natural light (75%), paddy field nearby household (51%), water filled open containers (44%), big plant near household (31%) and flower vases (26%) etc. Conclusion The known risk factors for dengue transmission were present in Haraincha Village Development Committee. Birat Journal of Health Sciences 2016 1(1): 3-7